Polymeric coatings in post-harvest conservation of fruits: An integrative systematic review (Research, Society and Development, 2025)
The use of polymeric coatings for postharvest fruit preservation has gained increasing relevance as a sustainable and efficient alternative to extend the shelf life of fresh produce. The present study aims to evaluate and synthesize the available evidence on polymeric coatings applied in fruit conservation. This study presents an integrative systematic review that evaluates the impact of different polymeric materials, both natural and synthetic, on fruits such as strawberries, guavas and cherry tomatoes. fifteen recent studies were analyzed, highlighting the application of polymers such as chitosan, pectin, PVA and electrospun films with essential oils. The results indicate that polymeric coatings significantly reduce weight loss, delay ripening and increase protection against pathogens. The application technique, coating composition and fruit characteristics were identified as determining factors for the effectiveness of the coatings. In addition, the adoption of biodegradable materials reflects the commitment to environmentally responsible solutions, while innovations such as nanoencapsulation of active compounds expand the preservation potential. The study concludes by pointing out gaps in the literature and suggesting new approaches to optimize the application of polymeric coatings in fruit preservation.